Increasing the benefits to disadvantaged groups in multistakeholder forestry negotiations - Center for International Forestry Research (Center for International Forestry Research, 2002)
This infobrief provides key points that will benefit disadvantaged groups in multistakeholder negotiations. Negotiations that include all the groups or stakeholders concerned should increase democratic decision-making and compromise. Experience has shown that the benefits that disandvantaged groups receive from multistakeholder negotiations depend on how the negotiations are done. This infobrief describes some of the pitfalls of multistakeholder negotiations and proposes ways for disadvantaged groups to avoid them.